Nutrient availability modulates the effects of plastic leachates on the growth and community dynamics of free-living freshwater bacteria - Schubert, Marius; Monikh, Fazel Abdolahpur; Yang, Yuyi; Grossart, Hans-Peter (Frontiers in Environmental Science, 2025)
IntroductionPlastic pollution poses a significant and increasing threat to aquatic ecosystems, i.e. contaminating water resources and posing health risks for humans and the environment. Yet, plastic leachates can also stimulate microbial growth and activities, impacting biochemical cycles in aquatic ecosystems. Synthetic polymers and their leachates vary in their chemical composition and thus differently impact micro- and higher organisms. This study aims to assess: i) how different synthetic polymer leachates affect free-living aquatic bacteria, and ii) how these effects vary at high vs. low nutrient conditions.MethodsLeachates were extracted from five synthetic polymers, i.e. low-density polyethylene (LDPE), polypropylene (PP), polyvinyl chloride (PVC), starch-polylactic acid (starch-PLA), and tire rubber via incubation in ultrapure water under UV radiation. Free-living (<5.0 μm) microbial communities of Lake Stechlin, Germany, were exposed to these leachates, and changes in total microbial growth and community composition were analysed using dose response models.ResultsNutrient availability resulted in different effects on total microbial growth and community composition of the tested synthetic polymers. For instance, PP leachates caused significant community shifts with increased total microbial growth rates at low nutrient conditions, but not at high nutrient conditions, whilst starch-PLA leachates led to community shifts at both nutrient conditions, but didn’t impact total microbial growth.DiscussionThese results highlight the importance of leachate quality and nutrient availability for understanding the effects of leachates on microbial growth and community dynamics. Our findings reveal that synthetic polymer pollution has the potential to alter microbial loop functioning and hence biochemical cycles of aquatic ecosystems.